Conceituando o papel do Messias: a concepção revolucionária de história em Walter Benjamin. - Nunes, Gabriel Galbiatti (2023)
The objective of this dissertation is to analyze how Benjamin conceptualizes the function and mode of action of the Messiah – the revolutionary classes – for the achievement of social emancipation. In the research, I start from the hypothesis that the role of the Messiah, in Benjamin’s thought, is strongly encapsulated in his conception of history. Consequently, in order to understand the proper behavior of the Messiah, according to Benjamin, it is first necessary to understand his conception of history. Therefore, I analyze Benjamin's conception of history, present in two distinct moments of his work: firstly, such conception present in the "Preface" to the book Origin of the German Tragic Drama; and the historical materialist conception of history, present in his texts from the 1930s – in particular, the theses "On the Concept of History" and "Archive N", from the Arcades. Based on the understanding of this conception of history, present in these two moments, I will analyze the text "Theological-Political Fragment", in which the thinker conceptualizes the task of the Messiah. To analyze this text, I return to Benjamin's conception of history, in order to demonstrate that the revolutionary classes execute an interruption of history that breaks with a continuum of catastrophes that accompany the defeated throughout history, thus freeing them from the injustices committed against them.